The belly fat cure fast track ebook Discover the ultimate carb swap™ and drop up to 14 bs. the first 14 days. - Cruise, Jorge (Hay House, Inc., 2011)
For years, fad diets and infomercials have overwhelmed you with unrealistic-and often unsafe-methods for losing belly fat quickly. It's time to know the truth. Avoiding hidden sugars-not calories-is the true key to weight loss. Combining this discovery with the burn-boosting power of the Ultimate Carb Swap, you will lose up to 14 lbs. in the first 14 days. This doctor-approved, science-based solution includes yummy foods such as cookies, pancakes, burgers, and even wine. So if you are ready to cure belly fat super fast with foods you already have in your kitchen, dig in!